2012
DOI: 10.1100/2012/835917
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Japanese Carbon Tax Reform Using the E3MG Econometric Model

Abstract: This paper analyses the potential economic and environmental effects of carbon taxation in Japan using the E3MG model, a global macroeconometric model constructed by the University of Cambridge and Cambridge Econometrics. The paper approaches the issues by considering first the impacts of the carbon tax in Japan introduced in 2012 and then the measures necessary to reduce Japan's emissions in line with its Copenhagen pledge of −25% compared to 1990 levels. The results from the model suggest that FY2012 Tax Ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…Activity of SOD or CAT was significantly higher in elderly hypertensives [ 356 ] and T2D [ 360 , 361 , 368 ] when compared with healthy controls. Increased SOD activity has been reported also in coronary artery disease patients [ 369 ] and in women with the polycystic ovary syndrome [ 370 ]. In patients with Crohn's disease, SOD and GPX increase during the active phase and return to normal during the remission phase [ 371 ].…”
Section: Redox Proteomic and Markers Based On Cysteine And Redox Ementioning
confidence: 99%
See 1 more Smart Citation
“…Activity of SOD or CAT was significantly higher in elderly hypertensives [ 356 ] and T2D [ 360 , 361 , 368 ] when compared with healthy controls. Increased SOD activity has been reported also in coronary artery disease patients [ 369 ] and in women with the polycystic ovary syndrome [ 370 ]. In patients with Crohn's disease, SOD and GPX increase during the active phase and return to normal during the remission phase [ 371 ].…”
Section: Redox Proteomic and Markers Based On Cysteine And Redox Ementioning
confidence: 99%
“…Simultaneously with increased MDA levels, significantly higher activities or levels of SOD and/or CAT were found [ 358 , 359 , 363 , 368 ]. Some studies reported unchanged or decreased CAT and/or GPX and elevated SOD and lipoperoxidation markers in T2D [ 360 , 361 , 412 ] and CVD [ 369 , 421 ]. The balance between SOD and CAT and/or GPX dictates H 2 O 2 levels that may potentially react with reduced metals.…”
Section: Measuring the Nonenzymatic Antioxidant Capacity In Body Fmentioning
confidence: 99%
“…Regarding the partial affirmation or negative attitude toward the effect of an environmental tax on emission reduction, the main research objects are concentrated in a single country or in the European Union and OECD as a whole [25][26][27][28][29][30][31]. In questioning the effect of specific environmental taxes on emission reduction, Lee et al found that Japanese carbon tax reform had only a small impact on emission levels by using a global macro-econometric model [43]. Fu et al also proved that a vehicle registration tax (VRT) as well as motor taxation exhibited little impact on carbon emissions alone.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2012, Australia introduced a carbon tax of $23 AUD per tonne of emitted CO2 on selected fossil fuels consumption [42]. Likewise, Japan introduced a carbon tax scheme in October 2012, aiming to reduce its greenhouse gas emission by 80% by 2020 [39]. Such regulations aim to eventually reduce emissions in all economic sectors, among which transportation is a main source of emissions.…”
mentioning
confidence: 99%